2012
DOI: 10.1002/prep.201100072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasonic Treatment for the Size Reduction of HNS and HMX in Comparison to Solvent‐Antisolvent Crystallization

Abstract: The paper presents and compares two methods for the synthesis of fine particles of the high explosives HNS and HMX by ultrasonic treatment and solvent/antisolvent crystallization. The effect of ultrasonic treatment on the particle size of explosives was studied by varying the amplitude and frequency of ultrasonication for different time periods using an ultrasonic probe and an ultrasonic bath. Solvent/antisolvent recrystallization was performed by varying the process parameters including stirring rate, antisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Purified HNS (mean diameter 90 mm with a range up to 600 mm) was dissolved at 10 g in 400 ml DMF (N, N-dimethylformamide) by heating to 65 8C and the HNS-DMF solution was filtered to remove any suspended material. Previously we had followed drowning out crystallization (designated as method 1) to make fine HNS wherein concentrated HNS solution in DMF (4 g in 80 ml) was poured slowly in a thin stream into the antisolvent water [13] which resulted in HNS of average diameter in submicron scale with a range extending to few microns and contained HNS particles not having nanoscale distribution. Subsequently in the present work in order to see the feasibility to make nano-scale HNS in bulk, this process was modified (designated as method 2) in antici-pation of having further lower particle size product and better control on a batch to batch size variation.…”
Section: Solvent-antisolvent Crystallizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Purified HNS (mean diameter 90 mm with a range up to 600 mm) was dissolved at 10 g in 400 ml DMF (N, N-dimethylformamide) by heating to 65 8C and the HNS-DMF solution was filtered to remove any suspended material. Previously we had followed drowning out crystallization (designated as method 1) to make fine HNS wherein concentrated HNS solution in DMF (4 g in 80 ml) was poured slowly in a thin stream into the antisolvent water [13] which resulted in HNS of average diameter in submicron scale with a range extending to few microns and contained HNS particles not having nanoscale distribution. Subsequently in the present work in order to see the feasibility to make nano-scale HNS in bulk, this process was modified (designated as method 2) in antici-pation of having further lower particle size product and better control on a batch to batch size variation.…”
Section: Solvent-antisolvent Crystallizationmentioning
confidence: 99%
“…It was used in solvent-antisolvent crystallization. For exploring the nano HNS preparation by solvent-antisolvent crystallization (UF-HNS) in bulk we modified the previously reported process [13] as our purpose was to standardize the method at least at a few grams scale per batch at the laboratory level. Dilute solution of HNS is desirable to make very fine nano-size particles but the good yield is also desirable.…”
Section: Particle Size and Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Kaur et al has evaluated ultrasonic treatment method with solvent-anti-solvent method for size reduction of HNS and HMX. It was observed that solvent and anti-solvent method produced HNS with size distribution up to 3 mm [18]. So it is seen from literature that many methods have been developed to prepare submicrometer explosive particles with tunable properties such as particle size, morphology and uniform size distribution.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%